Disaster at Djerba - Allen, Bruce Ware (History Today, 2017)
During a period of European peace, Spain sought to establish control of the Mediterranean. Yet a disastrous attempt to oust the Ottomans from North Africa threatened to accelerate the westward advance of Islam. Here, Allen talks about the Battle of Djerba.
Keywords: Invasions chrétiennes -- Djerba

On Board Communities: Social Groups, Motivations and On-Board Life Regulation of the Royal Fleet Against Djerba (1429-1432) - Molins, Pol Junyent (5th biennal conference 2017 Emotions, Imaginations, and Communities in the Medieval Mediterranean, 2017)
The reign of Alfons the Magnanimous (1416-1458) is an exceptional laboratory for the social study of war. Its recurrence and the different areas where the armies were mobilized are a unique setting for observation. And it is even more outstanding thanks to the vast amount of documentation preserved, which allows us to study the period in a much wider way. The aim of this paper would be to approach the human component of the medieval Catalano-aragonese armadas studying the particular case of the Royal fleet organised by King Alfons the Magnanimous in 1432 against de Tunisian island of Djerba. Often the motivation and relationship between the sea and the men who participated in such expeditions were very diverse, heterogeneous or even non-existent. The armada became somehow an exchange between social groups, sometimes forced, of different influences –economic, social, political, cultural- of different social status, communities of diverse territories and Kingdoms of the Crown of Aragon and, finally, between seafarers and landsmen.
Keywords: Invasions chrétiennes -- Djerba

Geographical and Social Origin of the Crews of the Catalano-Aragonese Royal Fleet Organized against the Tunisian Island of Djerba, 1430-1432 - Molins, Pol Junyent (Cohesion and Conflict in Iberian Maritime Borders during the Late Middle Ages: Insights from Otherness, 2017)
Keywords: Invasions chrétiennes -- Djerba